Rancang Bangun Tracking Pengiriman Berbasis Website Menggunakan Metode Systems Development Life Cycle (SDLC) dengan Model Waterfall - Prasetyo, Muhammad Farid Alif; Ardiansyah, Muhammad Rafly; Ashari, Adhitya Aryaputra; Putro, Daffa Tyan; Rahmawati, Endra (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
There are several business processes, namely account management employee data, and car data, then there is a road letter management business process where this business process the courier assigned to deliver the goods submits a road letter request which will be made and signed by the admin, then Tracking the car where in the business process after getting the road letter and the courier starts delivering the goods, the courier driving the car concerned manually enters the location and if it has reached the destination the admin recaps the data. This system will be designed using the PHP programming language and the Laravel framework, utilizing a MySQL database server that allows access from anywhere and anytime. The benefits obtained from this system are that it makes it easier for companies and owners to check the current location of goods, and ensure data transparency between different departments to avoid misinformation, and for testing using the black box method, all application features run well according to the plan that has been made.
Keywords: Design; UML; SDLC Methodology; Watefall Model; Black box Testing